Multifocal Dysembryoplastic Neuroepithelial Tumor: A Report of a Rare Case - Razmeh, Saeed; Sina, Farzad; Poranian, Maryam; Taheri Talesh, Jouan (Reports of Radiotherapy and Oncology, 2018)
Introduction: Dysembryoplastic neuroepithelial tumor (DNET) is a benign tumor commonly observed in young people and mostly in the temporal lobe. This tumor usually presents with seizure and involves glial and neuronal cells. Case Presentation: The current report presents a case of a 25-year-old female, with intractable seizures including complex partials and secondary generalized seizure. The brain magnetic resonance (MR) showed multiple nonspecific hyperintense lesions in the bilateral temporal lobe. The patient underwent surgery, and selective temporal lobectomy was performed. Conclusions: Microscopic examination showed multifocal DNET, and the patient was seizure-free after surgery. Although DNET is very rare, the presentation of this case can help with its diagnosis and treatment.